Absolute Authority Of Bawaslu In Handling Election Violations Post The Determination Of The National Results - Sumardi Efendi; Anisah Anisah; Mursyida Wara; Nur Okta Trisiyah (Seutia Hukamaa Cendekia, 2023)
Indonesia is a country that adheres to a democratic system, and the people are an essential element where people can freely express their opinions and choose leaders according to their wishes. Bawaslu exists as an election management body tasked with overseeing the implementation of elections throughout the territory of the Unitary State of the Republic of Indonesia. The purpose of this research is to see the absolute bawaslu authority in handling election violations post the determination of the national results, research methodology of literature studies, and review of Indonesian laws and regulations with the conclusion obtained by Bawaslu has the authority to receive and follow up on reports relating to alleged violations of the implementation of laws and regulations regarding elections before setting the results nationally. Bawaslu is not responsible for dealing with election violations after the determination of the results nationally, which is because the case was after the determination.